From Shattered Goals to Meaning in Life: Life Crafting in Times of the COVID-19 Pandemic - de Jong, Elisabeth M.; Ziegler, Niklas; Schippers, Michaéla C. (Frontiers in Psychology, 2020)
The novel COVID-19 pandemic has created an extraordinary situation for our generation, with many countries being on lockdown. With this, new situation comes many psychological challenges not only for health care workers and people suffering from COVID-19 but also for the general population. Adapting to the new situation can be demanding. Experts have suggested that emotions during this situation are very similar to grief, and people experience emptiness and sadness about the loss of their normal lives, which can even lead to a loss of meaning in life. In this paper, we argue that life crafting could offer a way to help people cope with the situation and renew their sense of meaning. A life crafting intervention is based on theoretical insights from multiple areas of research, like positive psychology, expressive writing, and the salutogenesis framework. Life-crafting interventions help people find meaning in life by focusing on their ideal future, and helping them set goals, and make concrete plans to achieve those goals and overcome obstacles. Since having a clear purpose or meaning in life has been shown to have many benefits, we propose that it can also help people to cope with the psychological effects of the pandemic. A life-crafting intervention can offer people a chance to evaluate their goals in a time of uncertainty and rediscover meaning in life to guide them through these difficult times.